2018
DOI: 10.1111/pbi.13032
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of amaranthin synthetase from Chenopodium quinoa and construction of an amaranthin production system using suspension‐cultured tobacco BY‐2 cells

Abstract: Summary Betalains are plant pigments primarily produced by plants of the order Caryophyllales. Because betalain possesses anti‐inflammatory and anticancer activities, it may be useful as a pharmaceutical agent and dietary supplement. Recent studies have identified the genes involved in the betalain biosynthesis of betanin. Amaranthin and celosianin II are abundant in the quinoa ( Chenopodium quinoa Willd.) hypocotyl, and amaranthin comprises glucuronic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 57 publications
1
19
0
1
Order By: Relevance
“…Nematode feeding experiments have shown that the ingestion of specific betalain pigments produce lifespan-prolonging effects [26,27]. In our recent investigation, we confirmed that amaranthin, a betanin glucuronide, inhibits HIV-1 protease activity; however, betanin did not exhibit significant inhibitory effects [14].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Nematode feeding experiments have shown that the ingestion of specific betalain pigments produce lifespan-prolonging effects [26,27]. In our recent investigation, we confirmed that amaranthin, a betanin glucuronide, inhibits HIV-1 protease activity; however, betanin did not exhibit significant inhibitory effects [14].…”
Section: Discussionsupporting
confidence: 68%
“…Together, these results strongly suggest that betanin and isobetanin, which are the main components of the red-beet betanin extract inhibit the aggregation of Aβ. Previous studies have reported that the biological effects of betanin include suppression of cancer cell proliferation [11,14] and low-density lipoprotein oxidation [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quinoa EBCs are involved not only in salt tolerance but also in resistance to ultraviolet (UV-B) stress 12,19 . Recently, our group and others sequenced an allotetraploid quinoa genome 9,20,21 and conducted gene functional analysis using the acquired data 22,23 . Furthermore, we generated quinoa mutants using ethylmethanesulfonate (EMS) and identified the genes responsible for several of the induced mutations 22 .…”
mentioning
confidence: 99%
“…Here, we show that ALSV-mediated transient expression techniques enable gene function studies in a wide variety of quinoa lines spanning all three sub-populations and can be used to alter the production of secondary metabolites such as pigments, carotenoids, and betalains, and also the plant morphology and architecture of quinoa. Although quinoa gene functions have been evaluated by the ectopic transient overexpression of exogenous genes in quinoa hairy roots, Nicotiana benthamiana leaves, and tobacco BY-2 suspension cells (Imamura et al, 2018(Imamura et al, , 2019(Imamura et al, , 2020, our findings presented here provide the quinoa research community with the gain-and lossof-function tools needed to analyze the functions of endogenous genes in planta and enable functional genomics in quinoa.…”
Section: Discussionmentioning
confidence: 99%